Insights into the molecular dynamics in polysulfone polymers from C-13 solid-state NMR experiments - Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Anto, Ralf; Bulakh, Neelima N.; Lele, Ashish K.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry B, 2015)
The molecular and segmental motions in three different grades of ductile polysulfone polymers; poly(ether sulfone) (PESU), polysulfone (PSU), and poly(phenyl sulfone) (PPSU) are probed using C-13 solid-state NMR experiments. Polarization inversion spin exchange at magic angle (PISEMA) experiments indicates that the phenyl rings in the polymers are undergoing pi-flip motions on the order of 100 kHz. The temperature dependent PISEMA experiments show that the fraction of mobile regions that undergoes aromatic pi-flips is higher in PPSU than in the other two polymers. The center band only detection of exchange (CODEX) experiments was carried out and was unable to detect any slow segmental motions in the chains. A combination of C-13 spin-lattice relaxation time (T-1) and T-1-filtered PISEMA experiments show that the mobile regions in all the polymers are dynamically heterogeneous.